PEMBUATAN PETA IDENTIFIKASI MASALAH DAN ANALISA POTENSI (IMAP) DESA MENGGUNAKAN APLIKASI Q-GIS - Sholahuddin, Moh; Safitri, Lusiana (Jurnal Abdimas Bina Bangsa, 2024)
Kendung Village is one of the villages located in Kedungadem District, Bojonegoro Regency which has an area of about 25,900 hectares and is directly adjacent to Lamongan Regency, so it is necessary to have a village administration map that can be used to provide information about the boundaries of the administrative area of Kendung Village and the infrastructure in the village. The purpose of this community service is to make a map to identify problems and analyze village potentials that can be used as a basis in village development planning. In making the map, it goes through several stages, including preparation, survey, and monitoring of the village fasos using GPS, digitizing village boundaries through google earth imagery, and the process of making maps using the QGIS application. This community service produced a map with geospatial information of the village area that contained problem identification and village potential analysis (PIPA)